Subungual squamous cell carcinoma leading to arm amputation - Ovidiu Fabian; Emilia Maria Pătruţ; Mădălina Șteţca; Radu Mircea Galasiu; Vlad Zolog; Adriana Zolog; Iacob Domşa; Ioan Șimon; Anca Mihailov; Olga Hilda Orăşan; Flaviu Mureşan (Journal of Mind and Medical Sciences)
Although rare, subungual carcinoma is the most common malignant nail tumor. The symptomatology is not characteristic, being very similar to that of other nail and periungual diseases. For this reason, early diagnosis is usually established by performing a biopsy. With appropriate treatment, subungual carcinoma usually has a favorable prognosis. Metastatic cases are rarely encountered, but they usually have a poor therapeutic result. This article presents the case of a patient with subungual carcinoma (diagnosed by histopathological exam), initially treated by amputation of the distal and middle phalanges of the fourth finger. Two years after the operation, a recurrence in the epitrochlear nodes was diagnosed, for which epitrochlear lymphadenectomy and postoperative chemotherapy were performed. At 7 months, metastases were detected in the axillary nodes, which were treated with radiotherapy and chemotherapy. The appearance and development of the tumor at the elbow and the lower third of the arm led the patient to accept scapulohumeral disarticulation. The patient finally adapted to the physical infirmity, having a good general condition and an optimistic attitude.